PCR based evidence of reticuloendotheliosis virus infection in chickens from turkey - Ongor, Hasan; Bulut, Hakan (My University, 2011)
In this study, presence of avian leukosis virus (ALV) and reticuloendotheliosis virus (REV) was investigated in neoplastic cases observed in breeder hens older than 20 weeks in commercial broiler breeders. Tumor samples were examined by PCR combined with primer sets specific for ALV and REV. It was found that the tumors were REV-originated. This is the first report showing the presence of REV infection in Turkey. © 2011 PVJ.
Keywords: Avian leukosis virus; Chicken; Reticuloendotheliosis virus; Tumor